Laparoscopic-assisted radical gastrectomy for distal gastric cancer - Du, Yian (AME Publishing Company, 2013)
A 48-year-old female patient was diagnosed with a superficial depressed type early gastric cancer (type IIc) of 1.0 cm at the gastric angle as indicated by gastroscopy. Laparoscopic-assisted greater omentum-preserving D2 radical gastrectomy was performed in combination with Billroth I reconstruction under general anesthesia for the distal gastric cancer on April 5, 2013. The postoperative recovery was satisfying without complications. The patient was discharged seven days after surgery.